2012
DOI: 10.4103/0022-3859.93246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cardiopulmonary bypass on tissue injury markers and endothelial activation during coronary artery bypass graft surgery

Abstract: The present study indicates that, despite comparable surgical trauma, the OPCAB significantly reduces tissue injury. The overall pattern of endothelial activation after OPCAB is significantly lower than that after CABG. This may contribute to improved organ function, and improved postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…It is widely used to determine perioperative myocardial injury after cardiac surgery and is an important indicator of the recovery of cardiac function and prognostic risk factors [19,20]. The present study has shown that the extent of myocardial injury after thoracoscopicASD repair was significantly lower than after conventional surgery, which is a prerequisite for the successful rehabilitation of patients who undergo cardiac surgery.…”
Section: Discussionmentioning
confidence: 49%
“…It is widely used to determine perioperative myocardial injury after cardiac surgery and is an important indicator of the recovery of cardiac function and prognostic risk factors [19,20]. The present study has shown that the extent of myocardial injury after thoracoscopicASD repair was significantly lower than after conventional surgery, which is a prerequisite for the successful rehabilitation of patients who undergo cardiac surgery.…”
Section: Discussionmentioning
confidence: 49%
“…Research has shown that the large pressure drop and shear stress across oxygenators in CPB is associated with hemolysis, leukocyte activation, and other inflammatory processes . This may be a significant cause of tissue injury via endothelial activation, increased neutrophil‐mediated cytotoxicity, or other factors . In this experiment, the Medos Deltastream DP3 exhibited a slightly greater pressure drop across the oxygenator, which may suggest a marginal increased risk of tissue injury.…”
Section: Discussionmentioning
confidence: 70%
“…В настоящее время известно, что операция в условиях искусственного кровообращения негативно влияет на эндотелиальную функцию [12]. К специфическим факторам хирургической агрессии в условиях искусственного кровообращения относятся контакт крови с чужеродной поверхностью контуров аппарата искусственного кровообращения, хирургическая травма, ишемически -реперфузионные повреждения, изменения температуры тела, вызывающие развитие системного воспаления [13].…”
Section: Discussionunclassified